Land use changes and ground dwelling beetle conservation in extensive grazing dehesa systems of north-west Spain - García-Tejero, Sergio; Taboada, Ángela; Tárrega, Reyes; Salgado, José M. (Biological Conservation, 2013)
Abstract Traditional management practiced over centuries in Mediterranean cultural landscapes has led to singular agrosilvopastoral ecosystems such as dehesas. Recent abandonment of dehesa management has resulted in shrub encroachment, habitat homogenisation and increased fire risk. Mechanical shrub cutting to decrease biomass load creates novel cleared dehesas with yet unknown consequences for the ecosystem function. We investigated the effects of these land use changes on ground dwelling beetles (carabids and staphylinids) as model organisms by comparing traditionally grazed, long-time abandoned and newly cleared dehesas. Land use changes affected beetle species composition by altering habitat structure (e.g., litter layer) and the availability of feeding resources. Grazed dehesas held the highest number of exclusive species and particular functional guilds of carabid seed eaters and staphylinid coprophiles, utilizing food resources related to the presence of grazing livestock (annual herbs and coprophagous insects). Beetle assemblages of abandoned dehesas, resembling those known from surrounding human disturbed oak forests, exhibited the lowest abundance and greatly differed from beetle assemblages of grazed dehesas. Shrub clearance after dehesa abandonment benefited opportunistic beetle predators feeding on decomposers associated with cutting slash left on the ground. The habitat structure and beetle species composition of cleared dehesas slightly approached those of grazed dehesas, therefore suggesting shrub cutting as a first step towards restoration of abandoned dehesas. However, since livestock grazing is an essential driver of ground dwelling beetle composition, it should be promoted after shrub cutting in cleared dehesas to restore the characteristic assemblages, species interactions and ecosystem function of grazed dehesas.
Keywords: Carabid and staphylinid assemblages; Functional guild of species; Land use abandonment; Oak savannah-like forest; Shrub encroachment; Traditional silvopastoral management